MYOPATHY ADVERSE DRUG REACTION ASSOCIATED WITH LANSOPRAZOLE: A CASE REPORT - Lidya Karina; Hanny Cahyadi (MPI (Media Pharmaceutica Indonesiana), 2018)
Proton pump inhibitor has been reported to cause myopathic adverse drug reactions in severaloverseas countries. Unfortunately, this case has never been raised and has not received much attentionin Indonesia. A case about myopathy associated with lansoprazole in 48-years old man has been recently reportedin Indonesia. Assessment methods used were time series data collection followed by causality analysisusing Naranjo Scale. The results of analysis revealed a Naranjo Scale of 9, which was interpreted as definite.This report concluded that lansoprazole could triggered myopathy adverse drug reaction in some sensitivepatient. The mechanism presumably through inhibition of H+K+-ATPase in other tissue which can leaddestruction of myofibril and leakage of calcium, pottasium, phosphate, myoglobin, creatine phosphokinase,lactate dehydrogenase, and aspartate transaminases from the muscle. This case report aims to remindhealth professionals to pay more attention at possible myopathy adverse drug reactions in the use of lansoprazoleand other proton pump inhibitors, so that more serious adverse drug reactions could be prevented.